THE EFFECT OF GIVING PINEAPPLE PEEL EXTRACT (Ananas comocus L.Merr) THROUGH DRINKING WATER ON THE DIGESTIVE SYSTEM OF JOPER CHICKENS - D.N.P.O., Kedisan; Siti, N. W.; Sriyani, N.L.P. (Jurnal Peternakan Tropika, 2024)
The study aimed to determine the effect of giving pineapple peel extract through drinking water on the digestive system of joper chickens. This research was conducted for 6 weeks at Sesetan Farm, Faculty of Animal Husbandry. The research used completely randomized design (CRD) with 4 treatments and 5 replications. Each replication used 3 joper chickens aged 2 weeks with a body weight of 100,31±11,4 g, so that 20 experimental units were obtained with a total of 60 joper chickens. The four treatments were joper chickens given drinking water without pineapple peel extract as a control (P0), joper chickens given drinking water with pineapple peel extract 6% (P1), joper chickens given drinking water with pineapple peel extract 8% (P2), and joper chickens given drinking water with pineapple peel extract 10% (P3). The variables observed were the percentage of liver, percentage of bile, percentage of pancreas, percentage of proventriculus, percentage of ventricle, percentage of small intestine, and the length of small intestine. The results of this study showed that the chickens treated with P0, P1, P2, and P3 gave significantly different results (P>0,05) on the percentage of the digestive system organs of joper chickens. Based on the results of the study it can be concluded that giving pineapple peel extract up to 6%, 8%, 10% gave the same results to the digestive system of joper chickens.